2004
DOI: 10.1002/cncr.20376
|View full text |Cite
|
Sign up to set email alerts
|

The utility of computed tomography scans in predicting suboptimal cytoreductive surgery in women with advanced ovarian carcinoma

Abstract: BACKGROUNDComputed tomography (CT) scans of the abdomen and pelvis may predict which patients with ovarian carcinoma can undergo optimal cytoreduction at primary surgery. Previous studies have demonstrated that patients with ovarian carcinoma had optimal cytoreduction rates ranging from 50–60%. The authors sought to determine whether these findings applied to a surgical practice with a higher rate of optimal debulking. A predictive model using CT scanning and CA 125 values would allow the authors to determine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
100
0
6

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(108 citation statements)
references
References 30 publications
(25 reference statements)
2
100
0
6
Order By: Relevance
“…Previous investigators assessing the utility of preoperative CT scan in this setting have retrospectively identified different radiologic predictors. [14][15][16][17][18] Axtell et al's analysis of 65 patients showed diaphragm disease and large bowel mesentery implants to be significant factors. 15 Dowdy et al's review of 89 patients found diffuse peritoneal thickening to be the only variable significantly associated with suboptimal debulking which is comparable to our study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous investigators assessing the utility of preoperative CT scan in this setting have retrospectively identified different radiologic predictors. [14][15][16][17][18] Axtell et al's analysis of 65 patients showed diaphragm disease and large bowel mesentery implants to be significant factors. 15 Dowdy et al's review of 89 patients found diffuse peritoneal thickening to be the only variable significantly associated with suboptimal debulking which is comparable to our study.…”
Section: Discussionmentioning
confidence: 99%
“…These scores were added together for a score of 0 to 10 which was compared to the surgical results. [14][15][16]22,23 Blood samples for measurement of CA125, within four weeks prior to surgery. CA125 was assessed by enzyme immunoassay (Roche E170) using a sandwich method with chemoluminescence.…”
Section: Pre-operative Assessmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…This modality of assessment, in experienced hands, has been shown to have PPV of 87% and NPV of 100% [20][21][22]. However, laparoscopic assessment requires an experienced surgical team and laparoscopic resources.…”
Section: Discussionmentioning
confidence: 99%
“…It is not completely understood whether the intrinsic biological behavior of the tumor or the skill of the surgeon is the main determinant of optimal cytoreduction. Several studies (2,6,(7)(8)(9)(10)(11)(12) have been performed to find preoperative methods or models on the basis of imaging, amount of ascites, serum marker CA-125 or molecular tissue markers that can predict the surgical outcome. As the prediction rates in these studies have a wide range, it is not clear whether the results are dependent on patient selection or type of hospital.…”
Section: Introductionmentioning
confidence: 99%